Middle cerebral artery aneurysms: aneurysm angiographic morphology and its relation to pre-operative and intra-operative rupture - Iracema Araújo Estevão; Bruno Camporeze; Antonio Santos de Araujo Jr; Breno Nery; Ápio Claudio Martins Antunes; Timothy R. Smith; Paulo Henrique Pires de Aguiar (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective Correlate the middle cerebral artery bifurcation aneurysm morphology with the pre-operative and intra-operative risk of rupture. Methods Forty patients with 46 middle cerebral artery bifurcation aneurysms were treated microsurgically by the same surgeon. Aneurysms were classified according to shape and the Fisher test was applied to analyze the effect of morphology on the pre-operative and intra-operative rupture. Results Pre-operative and intra-operative ruptures were observed in 8/46 patients (17.4%) and 14/46 patients (30.4%) respectively. Thirty-two cases (69.6%) had no symptoms postoperatively, modified Rankin score (MRS) of 0; 6.5% had MRS of 1 (no significant disability); 13% had MRS of 2 (slight disability); 4.3% had moderately severe disability (MRS of 4); and there were 3 deaths (6.5%) post-operatively. The morphology was not directly related to the rupture rate. Conclusion In general, ruptures are not affected by the morphology or the studied variables. Larger series are needed to validate these outcomes.